Sequence of infilling events in Gale Crater, Mars: Results from morphology, stratigraphy, and mineralogy. Issue 12 (6th December 2013) - Deit, Laetitia Le; Hauber, Ernst; Fueten, Frank; Pondrelli, Monica; Rossi, Angelo Pio; Jaumann, Ralf
Abstract [1] Gale Crater is filled by sedimentary deposits including a mound of layered deposits, Aeolis Mons. Using orbital data, we mapped the crater infillings and measured their geometry to determine their origin. The sediment of Aeolis Mons is interpreted to be primarily air fall material such as dust, volcanic ash, fine‐grained impact products, and possibly snow deposited by settling from the atmosphere, as well as wind‐blown sands cemented in the crater center. Unconformity surfaces between the geological units are evidence for depositional hiatuses. Crater floor material deposited around Aeolis Mons and on the crater wall is interpreted to be alluvial and colluvial deposits. Morphologic evidence suggests that a shallow lake existed after the formation of the lowermost part of Aeolis Mons (the Small yardangs unit and the mass‐wasting deposits). A suite of several features including patterned ground and possible rock glaciers are suggestive of periglacial processes with a permafrost environment after the first hundreds of thousands of years following its formation, dated to 3.61 Ga, in the Late Noachian/Early Hesperian. Episodic melting of snow in the crater could have caused the formation of sulfates and clays in Aeolis Mons, the formation of rock glaciers and the incision of deep canyons and valleys along its flanks as well as on the crater wall and rim, and the formation of a lake in the deepest portions of Gale.